Relationships between fault characteristics and seismic responses in a large lab-scale tri-axial injection test conducted on a faulted Castlegate Sandstone. (September 2022) - Babarinde, Oladipupo; Stanchits, Sergey; Bauer, Robert; Frailey, Scott; Oye, Volker; Sweet, Dustin
Abstract: To investigate mechanisms causing microseismicity (Mw < 2) at a CO2 injection site, a large-scale triaxial block experiment was carried out on a faulted (saw-cut) cubic-meter of Castlegate Sandstone. The experiment consisted of injection tests at varying differential stresses, while monitoring and recording pore pressure and acoustic emissions (AEs). During the experiment, ∼33, 000 AEs and ∼14 mm of horizontal displacement/slip, like a strike-slip fault movement, occurred. To understand the AE responses and ascertain fault characteristics near the located AEs, we modeled the topography of the fault surface, fault aperture, and fault-gouge thickness using pre- and post-experiment laser scans of the fault surface on each half of the block. Additionally, we characterized surface roughness parallel and perpendicular to slip. Models show crushing and flattening of the fault surfaces can be linked to the spatiotemporal distribution of AEs within 50 mm of the fault surface. Approximately 65% of AEs were in areas with small aperture (≤300 μm); thicker fault gouge was observed in adjacent areas with wider aperture and shows a two-fold reduction in grain size relative to unaltered Castlegate Sandstone. This work provides a conceptual understanding on fault surface evolution, which can be applied towards modeling of seismic slip. Highlights: Injection test on a polished saw-cut fault surface of a large block of Castlegate Sandstone showed activation of fault slip. Topography of a fault or fracture surface influences spatiotemporal seismic responses. Fault surface roughness fits a self-affine model. The mean and mode of the grain size of produced fault gouge is around two-fold smaller than the unaltered rock. Fault gouge preferentially accumulates in fault surface topographic lows.